The five-point heart healthy lifestyle - Opie, Lionel H. (SA Heart Journal, 2017)
The “Lifestyle Big-Five” are, in order of importance, nonsmoking, daily exercise for 30 min or more, a body mass index of 25 or less, the ideal diet  and last and least, modest alcohol. This lifestyle is associated with a pattern of maximal freedom from cardiovascular disease, stroke and with improved longevity. The major data supporting the “Lifestyle Big-Five” chiefly come from the results of the Nurses’ Health Study over 26 years and the Health Professionals Study over 20 years, both in the USA. Both these studies are supported by several large European studies including one that by computer randomly recruited a selected population. Apart from the evidence for non-smoking, which is already well-established and well-known, each of the other four components are evaluated in this review, with recommendations for application to patients. SAHeart 2011; 8:154-163